Making sense language of leadership and Pakistani identity through Mr. Imran Khan's discourse - Irfan, Faisal (2025)
Language serves as a primary medium of communication between the speaker and the listener. Furthermore, language and politics go hand in hand, as learning and comprehending political genre is to learn a language created for codifying, extending and transmitting political discourse in any text/talk. Language of political leaders might be one of the most challenging types of discourse, because it is usually characterised by the use of different techniques and strategies that allow political leaders to persuade people of their ideologies and thoughts for the construction of identities. In language of leadership, the strategy of convincing the audience to believe on what a leader says is very crucial. Therefore, balancing good persuasive strategy and speech delivery can make the political leaders produce an effective persuasive speech to maintain their identities. The present thesis examines the role of language of leadership and Pakistani identity in the spoken discourse of former Pakistan Prime Minister Mr. Imran Khan. Thus, this qualitative study explores the former Prime Minister of Pakistan, Mr. Imran Khan‘s language of leadership and Pakistani identity through his spoken discourse. More specifically, it reports the study which explores the language used during his leadership nationally and internationally. The data of the study were carefully collected from the content of the ten international interviews and ten international speeches of Mr. Imran and analysed based on the theoretical framework of Fairclough's three-dimensional model. Ten participants were selected for in-depth interviews to explore the opinions of Pakistani people on Mr. Imran Khan's language as a political leader. The findings indicate that Mr. Imran employed linguistic and rhetorical strategies in demonstrating his leadership in Pakistan and abroad as reflected in the spoken discourse. His persuasive and strong rhetoric clearly informed the world of his standpoints. He uses inclusive pronouns rather excessively to persuade the world communities on how to manage ecological and global issues. The study investigates not only the way identities are constructed and defended through language, but also their significance in shaping the professional image of Mr. Imran Khan. The study contributes to a deeper understanding of leadership language, Pakistani identity and its persuasiveness suggesting how they should be enhanced for better understanding particularly among future scriptwriters, learners of English language and political science students